Factors Correlate to Farmers' Indebtedness in Suwannaphum District, Roi Et Province - Kratupunya, Pimchanok; Chairatana, Pirada; Gohwohg, Srirath (Journal of Modern Learning Development, 2021)
This research has objective to 1) Study correlate to farmers' indebtedness in Suwannaphum district, Roi Et province 2) Compare factors of farmers' indebtedness in Suwannaphum district, Roi Et province 3) Study the correlation between personal financial management factors and the farmers' indebtedness factors at Suwannaphum district, Roi Et province 4) Study the correlation between factors of consumption behavior and factors of farmers' indebtedness at Suwannaphum district, Roi Et province. The sample in this research was 400 farmers who have debt with Bank for Agriculture and Agricultural Cooperatives (BAAC), Suwannaphum district, Roi Et province. Tools used for data collection was a questionnaire. Statistics used for data analysis were percentage, mean, standard deviation, t-test, one-way analysis of variance, and the Pearson correlation coefficient by setting statistical significance at the level of .05. The results of the hypothesis test showed the samples with the different average monthly expenditures had different indebtedness factors with the statistical significance at the .05. While the sample with the differences in gender, age, agricultural type, marital status, education level, number of family members, and average monthly income did not show the differences among indebtedness factors. The Personal financial management factors including short-term financial planning and long-term financial planning have a low level of correlation and in line with the factors of farmers' indebtedness in Suwannaphum district, Roi Et province at the statistically significant level of .05. The consumption behavior factors including stimulant and purchasing decisions had a low level of correlation and in line with the factors causing the farmers' indebtedness in Suwannaphum district, Roi Et province with a statistically significant level of .05. The perception did not have a correlation with farmers' indebtedness factors in Suwannaphum district, Roi Et province.